2004
DOI: 10.4049/jimmunol.173.6.4120
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Signaling Lymphocytic Activation Molecule Triggers a Signaling Cascade That Enhances Th1 Responses in Human Intracellular Infection

Abstract: T cell production of IFN-γ contributes to host defense against infection by intracellular pathogens, including mycobacteria. Lepromatous leprosy, the disseminated form of infection caused by Mycobacterium leprae, is characterized by loss of cellular response against the pathogen and diminished Th1 cytokine production. Relieving bacterial burden in Ag-unresponsive patients might be achieved through alternative receptors that stimulate IFN-γ production. We have previously shown that ligation of signaling lymphoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 56 publications
0
27
0
Order By: Relevance
“…Positive and negative signals delivered by the interaction of several costimulatory molecules with their receptors are required to mount an effective immune response during T‐cell activation. Previously, we demonstrated that SLAM/SLAM signaling increases cell‐mediated immunity in response to Mtb ; 9 while SAP, through interaction with SLAM, interferes with IFN‐γ production during mycobacterial infection 9 , 35 . NTB‐A, another member of SLAM family, increases Th1 cytokine production 10 and participates, in association with SAP, in the induction of tolerance and cellular homeostasis 12 , 38 .…”
Section: Discussionmentioning
confidence: 99%
“…Positive and negative signals delivered by the interaction of several costimulatory molecules with their receptors are required to mount an effective immune response during T‐cell activation. Previously, we demonstrated that SLAM/SLAM signaling increases cell‐mediated immunity in response to Mtb ; 9 while SAP, through interaction with SLAM, interferes with IFN‐γ production during mycobacterial infection 9 , 35 . NTB‐A, another member of SLAM family, increases Th1 cytokine production 10 and participates, in association with SAP, in the induction of tolerance and cellular homeostasis 12 , 38 .…”
Section: Discussionmentioning
confidence: 99%
“…The former signals through STAT4, which binds to a site 236 bp upstream of the IFN-γ start codon [13], and the combination of IL-12 and IL-18 up-regulates binding of AP-1 transcription factors to the −196 to −183 bp region [13]. In addition, we previously reported that SLAM, a transmembrane signaling receptor that influences cytokine production by activated T cells, enhanced IFN-γ secretion in response to mycobacteria through a signaling cascade that increased activation of NFκB and T-bet [14]. In the current study, we demonstrated that ~80% of antigen-induced SLAM + T cells expressed pCREB, that blocking SLAM with siRNA markedly reduced pCREB, and that engaging SLAM with agonistic monoclonal antibody stimulated pCREB expression.…”
Section: Discussionmentioning
confidence: 99%
“…SLAM, which is a surface receptor expressed on lymphocytes and DCs, can induce IFN-γ production and proliferation in T cells by direct upregulation of T-bet. In addition to T-bet, SLAM can induce expression of Stat1 and NF-κB (Quiroga et al, 2004), i.e., transcription factors that may also play a role in the activation of the IFN-γ gene. Furthermore, T-bet is induced by the co-stimulatory receptors GITR (Patel et al, 2005) and Sema4a (Kumanogoh et al, 2005), as well as by the signal transducer p38 Mitogen-Activated Protein (p38MAP) …”
Section: Induction Through Costimulatory Factorsmentioning
confidence: 99%